Comparative in vitro study of a new silicone mouth swab for soft tissue cleaning under wet and dry brushing conditions - Nutthawadee Engsomboon; Bhornsawan Thanathornwong; Siriwan Suebnukarn (Scientific Reports)
Abstract The use of silicone mouth swabs for soft tissue cleaning in elderly care is significant as it offers a gentle yet effective solution for maintaining oral hygiene, particularly in patients with limited dexterity or cognitive impairments, thereby reducing the risk of oral infections and improving overall health. This study aimed to compare the pseudo-plaque cleaning efficiency of a newly designed silicone mouth swab with that of the existing MouthEze (MC3) under both wet and dry brushing conditions. A new silicone mouth swab was designed with both straight and threaded brushing bristles and a longer head length of 24.0 mm, compared to the MC3, which has only straight bristles and an 18.0 mm head. A pseudo-plaque, created by mixing 6.0 g of Thicken Up Clear food additive with 12.0 ml of water and food coloring, was spread onto a NISSIN dentoform silicone rubber sheet with a thickness of 2.0 mm. The MC3 silicone head (n = 12) and the new silicone head (n = 12) were attached to a V.P.2000 tooth brushing machine, operating at 75 rounds per minute with a force of 2.45 N, and each was used to brush the surface 25 times under both wet (n = 12) and dry (n = 12) conditions. The ImageJ program was used to analyze and quantify the area where the pseudo-plaque was removed after brushing. A two-way analysis of variance (ANOVA) was conducted to assess differences in pseudo-plaque removal between groups. The pseudo-plaque removal per head length of the new silicone mouth swab was significantly higher than that of the MC3 under both wet brushing (72.30 ± 10.21 mm2 vs. 53.69 ± 5.66 mm2, p < 0.05) and dry brushing conditions (66.82 ± 11.29 mm² vs. 53.33 ± 8.54 mm2, p < 0.05). The new silicone mouth swab with both straight and threaded brushing bristles and a longer head length was more effective in pseudo-plaque removal than the swab with only straight bristles and a shorter head.